Cartilha digital de orientações para o autocuidado em pacientes com uso de bomba elastomérica para quimioterapia - Aranha, Alcy Leal (2023)
According to the type of chemotherapy protocol for the treatment of cancer, it is possible to use an infusion system called an elastomeric pump, which has, among other facilities, the possibility of infusing the chemotherapy drug at the patient's home, without necessarily having to stay hospitalized. But for the use of this device, some self-care actions and monitoring must be observed, so that there is no delay or advance in the infusion. Supported by Dorothea Orem's theory of self-care and the standards for preparing educational material in health, this study proposes a digital booklet used by patients using an elastomeric pump for chemotherapy. General Objective: To build and validate a digital guide for self-care in patients with cytotoxic chemotherapy infusion using an elastomeric pump. Methodology: This is a methodological study in which the development stages have been grouped into two sections. The first refers to the organization of the content. An Integrative Review of the literature was carried out, followed by a mapping of the guidelines practiced by professionals specializing in chemotherapy. In the second section, the digital booklet was constructed. For this stage, the construction was supported by the theoretical references of Echer (2005) and Silva (2017), followed by face validation with the user of the technological product, using the prototype of the digital booklet. After this validation, the technological product was finalized and hosted on the web platform. This section concludes with the registration of the technological product. Construc Result: In the construction of the content and the literature search, 17 precautions were listed. In the survey of 44 professionals in clinical practice, 42 self-care guidelines were proposed. These were grouped into a single list of 16 fundamental guidelines for the self-care of patients using elastomeric pumps. These were classified according to the level of scientific evidence. After this survey, it was possible to construct the Guide to Self-Care During Infusion with an Elastomeric Pump. This guide was validated with 20 patients using this infusion modality, to validate the objective, content, relevance and usability of the digital booklet. Product developed: A digital booklet with guidelines for self-care, used as an orientation tool by the nurse and a guide for the patient. Conclusion: The digital booklet entitled Guide to Self-Care during Infusion with an Elastomeric Pump, based on the theoretical framework of Dorothea Orem's Self-Care Theory, provides a safe and friendly way for cancer patients to adapt to the new self-care needs required by their treatment modality. It provides continuous access to the information provided by the nurse during the nursing process.